2008
DOI: 10.1158/1535-7163.mct-08-0051
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 inhibits prostate tumor growth through endothelial apoptosis

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is an important endogenous inhibitor of urokinase-type plasminogen activator. Its action in tumor angiogenesis is complicated, varying with experimental setting and its cellular origin. To further understand the mechanism of the effect of PAI-1 on tumor angiogenesis, especially newly established tumor vasculature in early tumor progression, stable transfectants (TO-PAI-1) of the human prostate adenocarcinoma, PC3, were generated in which PAI-1 expression is under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Previous studies have shown that cell adhesion is associated with vulnerability to apoptosis (28, 29). Here, we confirmed that the suppression of PAI-1 resulted in a significant dose–response reduction in cellular adhesion in parental T24, UM-UC-14, and UROtsa cells after pretreatment with tiplaxtinin for 30 minutes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that cell adhesion is associated with vulnerability to apoptosis (28, 29). Here, we confirmed that the suppression of PAI-1 resulted in a significant dose–response reduction in cellular adhesion in parental T24, UM-UC-14, and UROtsa cells after pretreatment with tiplaxtinin for 30 minutes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether PAI-1 protects (myo)fibroblasts from apoptosis in old mouse lung through inhibiting plasmin activity, caspase-3 activity, or p53 expression remains to be determined. We also want to point out that although PAI-1 protects fibroblasts from apoptosis (Chang and others 2010; Horowitz and others 2008; Huang and others 2012; Zhang and others 2013), opposite effects have been observed in other types of cells (Abderrahmani and others 2012; Bajou and others 2008; Bhandary and others 2013; Chen and others 2008; Shetty and others 2012). Whether PAI-1 expression is increased with age in other types of cells in the lung and how PAI-1 regulates apoptosis sensitivity in these other types of cells is unknown and is under active investigation in this lab.…”
Section: Discussionmentioning
confidence: 98%
“…These findings convincingly indicated that PAI-1 played an important role in the pathogenesis of BLM-induced lung fibrosis and that inhibition of PAI-1 expression with siRNA might be a potential therapeutic target for treatment of lung PAI-1 regulates a variety of cellular processes, including adhesion, migration, detachment, angiogenesis, proliferation and apoptosis, in vitro and in vivo [19,20] . PAI-1 is a paradoxical protein that exerts different effects in various cell lines [21][22][23][24] . Previous studies have shown that PAI-1 could protect fibrosarcoma cells from etoposide-induced apoptosis [25] and augment the proliferation of vascular smooth muscle cells [26] .…”
Section: Discussionmentioning
confidence: 99%